2008
DOI: 10.1097/mlr.0b013e31815cecd8
|View full text |Cite
|
Sign up to set email alerts
|

Age and Racial/Ethnic Disparities in Arthritis-Related Hip and Knee Surgeries

Abstract: These national data document lower rates of arthritis-related hip/knee surgeries for older black versus white adults age 65 or above, consistent with other national studies. However, utilization rates for black versus white under age 65 do not differ. Lower utilization among Hispanics versus whites in both age groups is largely explained by medical access factors. National utilization patterns may vary by age and merit further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 31 publications
4
75
0
Order By: Relevance
“…The effect of BMI on TKA survivorship is unclear. Women may have a greater propensity toward obesity, and obesity in African-American females (38%) is more prevalent than for Caucasian females (26%) [6]. This contrasts a study that observed no difference between genders in OA prevalence [4].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The effect of BMI on TKA survivorship is unclear. Women may have a greater propensity toward obesity, and obesity in African-American females (38%) is more prevalent than for Caucasian females (26%) [6]. This contrasts a study that observed no difference between genders in OA prevalence [4].…”
Section: Discussionmentioning
confidence: 75%
“…Dunlop et al [6] reported a higher prevalence of OA in the African-American (40%) and Hispanic (44%) populations of noninstitutionalized individuals 70 years and older when compared with a nonHispanic Caucasian (25%) population [6]. However, there is little association between OA disease rates and use of TKA among racial subgroups: disease rates in African-Americans are increasing compared with rates seen in Caucasians, whereas use rates are trending in the opposite direction [15,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethnic and racial disparities in care have been documented in many treatment realms [5][6][7]11]. Epstein et al [7] found ethnic minorities were less likely to be treated by highvolume surgeons at high-volume hospitals, with African Americans operated on by low-volume surgeons in lowvolume hospitals in nine of 10 procedures across the surgical spectrum studied at New York City area hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the documented benefits of TKA, racial and ethnic disparities have been reported in the utilization of TKA in the United States [2,4]. In addition to the disparities in TKA utilization, studies have also demonstrated disparities with respect to outcomes and complications of TKA [28].…”
Section: Introductionmentioning
confidence: 99%